Pengembangan Media Pembelajaran Komputer Berbasis Simulasi untuk Materi Menulis Puisi di Kelas X SMK Al-Washliyah - Putri, Nevia Sefiana; Ali, Ali; Rita, Rita (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2024)
This study aims to evaluate the feasibility and effectiveness of computer-based learning media with a simulation model for poetry writing in class X at SMK Al-Washliyah. The research employs a research and development (R&D) approach, encompassing steps such as data collection, planning, product development, initial field trials, revisions, further trials, product refinement, field implementation, final adjustments, and dissemination. The population and sample of the study comprised 30 students. Results indicate the media's high feasibility, with media experts rating it "Very Eligible" at 84% and 89%, respectively, and material experts rating it at 96% and 94.6%. Teacher assessments also rated it "Very Eligible" at 96%, and field tests with 30 students yielded a score of 87.6%. The effectiveness evaluation, measured through an assessment test post-implementation, resulted in a "Highly Effective" rating with a score of 83.9%.